The effects of education through short message service for mothers on sleep duration among school-aged children: A randomized trial - Zeynab Mousarrezaei; Leila Valizadeh; Mahasti Alizadeh; Parvaneh Aghajari; Mohammad Asghari Jafarabadi; Raheleh Janani (Kashan University of Medical Sciences, 2020)
Background: Children's sleep problems can negatively affect their daily functioning at home and school, their behaviors, and their health status. Education through short message service (SMS) is among the techniques with potential positive effects. However, no study is available on the effects of SMS-based sleep education on sleep among children. Objectives: This study aimed to examine the effects of SMS-based education for mothers on sleep duration among their 7-12-year-old children who had sleep inadequacy. Methods: This randomized controlled trial was conducted on 206 elementary students and their mothers. Students with sleep inadequacy who were selected from thirteen elementary schools in Tabriz, Iran, were randomly allocated to a control (n = 103) and an intervention (n = 103) group. In the intervention group, students' mothers were provided with sleep education through thirty nightly messages sent at 20:00 for 1 month. Mothers in both groups completed the 2-week sleep record before, 1 week, and 3 months after the intervention. The data were analyzed using the independent samples t- and the Chi-square tests, the repeated-measures analysis of variance, and the analysis of covariance. Results: The mean of sleep duration in the intervention group significantly increased from 533.28 ± 29.35 min at baseline to 551.26 ± 37.93 at the first posttest and 568.25 ± 35.44 at the second posttest (P < 0.05). In the control group, the mean of sleep duration significantly increased from 523.13 ± 33.69 min at the pretest to 539.98 ± 49.03 at the first posttest (P < 0.05) and insignificantly decreased to 528.96 ± 52.20 at the second posttest (P > 0.05). Between-group difference respecting the mean of sleep duration was statistically significant only at the second posttest (P < 0.001). Conclusion: SMS-based sleep education for mothers is effective in significantly increasing sleep duration among school-aged children.